A Comparative Analysis of Profit Rate on Deposit in Islamic Banks in Bangladesh - Kabir, Mohammad Rokibul; Chowdhury, Abdul Hamid (IIUC Studies, 2016)
The study is based on a total number of seven full-fledged listed Islamic Banks operating in Bangladesh. Secondary sources of data are used in this research. Data were collected from the Website of Bangladesh Bank and studying relevant literatures. This paper examines whether there is any differences of profit rate on deposits among different Islamic Banks. It also aims at finding whether there is any relationship between inflation and profit rate on deposits. Analyses have been done for two types of deposits accounts called Mudaraba Term Deposits Account and Mudaraba Savings Account. The results of the study reveal that, in case of Term Deposits the highest mean return is 11.06458% as offered by the First Security Islamic Bank Ltd. and the lowest mean return of 8.687500% is offered by Export Import Bank of Bangladesh Ltd. while in case of Mudaraba Savings Deposits the highest mean return of 6.583333% is offered by the First Security Islamic Bank Ltd. and the lowest mean return of 4.330417% is offered by Al Arafah Islami Bank Ltd. during the studied period. One sample t-test has been applied to find whether there is any significant difference in profit rate in different months and the study unfolds that the profit rate differs significantly in all the banks from month to month. The findings of Paired Sample t-test suggests that there is a significant difference in mean return between the Islamic banks in both of the Mudaraba Term Deposits and Mudaraba Savings Accounts in all the cases except for two pairs as the return on savings deposit does not significantly differ between Al Arafah Islami Bank Ltd. and Social Islami Bank Limited while it does not differ significantly between Social Islami Bank Limited and Islami Bank Bangladesh Ltd. in case of Mudaraba Term Deposits. Finally, the relationship between inflation and rate of profit is found insignificant in case of Mudaraba Saving Deposits while significant relationship has been discovered between Mudaraba Term Deposits and rate of inflation. IIUC Studies Vol.10 & 11 December 2014: 81-98